In-situ cellulose-framework templates mediated monodispersed silver nanoparticles via facile UV-light photocatalytic activity for anti-microbial functionalization. (1st October 2021) - Ko, Sung Won; Lee, Ji Yeon; Rezk, Abdelrahman I.; Park, Chan Hee; Kim, Cheol Sang
Abstract: Cellulose is well known as a biocompatible material or natural reducing material. In this study, As an eco-friendly and facile method, we prepared monodispersed silver nanoparticles (AgNPs) in cellulose-framework through photocatalytic reaction. and we fabricated electrospun fiber scaffolds with excellent antibacterial properties and biocompatibility. UV-irradiation causes the electrical change of the cellulose-framework, thereby converting Ag ions into Ag particles. We applied a three-electrode system to confirm the phenomenon. Through STEM and EDS, it was found that the synthesized AgNPs were monodisperse in the nanofibers, and antibacterial activity was confirmed using gram-negative and gram-positive bacteria. In addition, it was suggested that the gradual release of simvastatin contained in the nanofibers and excellent mineralization would be easy to apply to bone regeneration. Therefore, the manufactured composite electrospun fiber mat can be used not only in biomedical fields but also in various applications that need to prevent the accumulation of microorganisms. Highlights: UV-light assisted silver nanoparticles synthesis via cellulose-based reducing agent. Monodispersed silver nanoparticles embedded in scaffolds to prevent side-effects. The change in surface charge was verified by electrochemical method. Excellent antimicrobial ability as a scaffold for insertion into the human body.